Beneficial Effects of Fennel (Foeniculum Vulgare) in Treating Obesity in Rats - A. Elghazaly Nawal; H. Radwan Eman; H. Zaatout Hala; M. Elghazaly Mohamed; El din Allam Nour (Journal of Obesity Management, 2019)
Obesity is associated with a number of serious medical complications, which are often referred to as the “insulin resistance syndrome”. The aim of the present study was performed to investigate the possible interaction between a conventional drug used for management of cholesterol and traditional herbal remedies on the obesity. This was carried through out: through estimation of blood test; Estimation of serum tests; Determination of oxidative stress biomarkers and the antioxidant enzymes activities in the liver were assayed; Histopathological examination of the liver and kidney of adult male albino rats were done. In the present study, the serum levels of the total protein and albumin in the obesity group (7.1± 0.2) and (4.78 ± 0.19); respectively were significantly (p ≤ 0.05) more than those of the control group (6.5±0.1) and (3.95± 0.1).The administration of (fennel group) revealed significant (P<0.05) decrease in the serum levels of the albumin and total protein (4.38± 0.1) and (6.65± 0.2); respectively as compared to the obesity group (4.78 ± 0.19) and (7.1± 0.2(. The total cholesterol of the group(5) (fennel and ator) after two weeks from a high fat diet than treatment with fennel and Ator through six weeks equal 142.86±5.9, 100.4±8.68, 93.29±5.99, 87.1±11.28, 80.4±21.55, 78.1±6.7 and 77.1±6.87; respectively. The present study showed a significant (P<0.05) increase in the activities of ALT, AST and ALP in the obesity group which recorded as (60.5±11.45), (57.25±6.3) and (845.0±49.47); respectively as compared to the control group (28.25±1.7), (38.5±3.87) and (537.0±41.5); respectively. The fennel group caused significant decrease in the activities of these enzymes (41.0± 2.9), (42.25+3.2) and (717.75+48.6); respectively compared to the obesity group. Ator group showed a significant decrease in the activities of these enzymes (40.0±2.16), (42.5±3.1) and (679.25±41.16); respectively compared as obesity group. The activity of AlT, AST and ALP in the fennel and ator group (32.75±2.5), (40.5±2.38) and (601.25±17.5); respectively were near to the control group.
Keywords: Fennel -Foeniculum vulgare- Atorvastatin- obesity- histopathology-rats-herb